The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/1440-1703.12006
|View full text |Cite
|
Sign up to set email alerts
|

Summer and winter ecosystems of the world ocean photic zone

Abstract: The increased availability of global scale environmental and biological data is enabling more objective, data‐driven, classifications of the oceans. However, comparisons of seasonal differences at a global scale have been limited to ocean color and derived variables. Here, we used long‐term averages of 18 ocean variables in summer and winter to classify the seasonal ocean surface waters through principle components analysis and k‐means clustering. We identified 11 distinct areas that fit the definition of “eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Similarly, based on ginland analyses key variables are related to high temperature velocity of change (sst_max_sl) and sea surface salinity (SSS) of the freshest month (biogeo09), indicating that reproduction and survival are important forces acting on sardines in the area. The only variables that reflected northern poorness to southern richness were mean PAR (photosynthetically active radiation) and bottom nitrate, which have been found to vary on a seasonal basis (Zhao & Costello, 2019). Nevertheless, not strictly looking into the seasonal variation of the environmental variables with time (we only looked at average values for the period May–October approximating the conditions prior to the species' reproductive season, Gordó‐Vilaseca et al, 2021) inevitably disregards any seasonal/temporal changes occurring as well as their spatial extent, with the role of seasonality remaining to be further assessed in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, based on ginland analyses key variables are related to high temperature velocity of change (sst_max_sl) and sea surface salinity (SSS) of the freshest month (biogeo09), indicating that reproduction and survival are important forces acting on sardines in the area. The only variables that reflected northern poorness to southern richness were mean PAR (photosynthetically active radiation) and bottom nitrate, which have been found to vary on a seasonal basis (Zhao & Costello, 2019). Nevertheless, not strictly looking into the seasonal variation of the environmental variables with time (we only looked at average values for the period May–October approximating the conditions prior to the species' reproductive season, Gordó‐Vilaseca et al, 2021) inevitably disregards any seasonal/temporal changes occurring as well as their spatial extent, with the role of seasonality remaining to be further assessed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, our observed responses to local environments comply with the environmental conditions prevailing in those areas and their deterioration (Ramírez et al, 2021). According to the marine regionalization of Zhao and Costello (2019), there are extreme changes in PAR, waves and wind in the northern sites (i.e., GSA07a, GSA07b and GSA06a) during winter (December–February) but high PAR during summer (June–August) at the southern sites with consequent effects on productivity and temperature, especially during the reproductive period. The above, coupled with rapid changes in temperature (Ramírez et al, 2018, 2021), could be held responsible for such differences in physical conditions between the north and the south that might be reinforced by periods of lower connectivity with areas subject to milder pressures of extreme environmental variability and where healthier fish are found, such as the GSA06c sampling site (as in Hidalgo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This advances previous MPA classifications for the world (Selig et al, ) and Coral Triangle (Asaad, Lundquist, Erdmann, & Costello, ) that lacked ecosystem layers for biodiversity mapping. Likewise, following the similar approach we explored potential variations along the boundaries between marine ecosystems due to seasonal change (Zhao & Costello, ). We found that there were little change in tropic zones, latitudinal changes in high latitudes, and more complicated changes in other regions.…”
Section: Discussionmentioning
confidence: 99%
“…A striking feature is the five subtropical gyres with the lowest primary productivity that have been referred to as "ocean deserts" [38]. They did not change greatly across the seasons [39], but they are strongly influenced by vertical mixing and nutrient delivery [30]. The centers of the gyres are easily located and displayed in Figure 2b with Chl-a of 0.033 mg/m 3 (G1), 0.043 mg/m 3 (G2), 0.044 mg/m 3 (G3), 0.022 mg/m 3 (G4), and 0.036 mg/m 3 (G5), respectively.…”
Section: Mean Chl-amentioning
confidence: 99%